Penilaian Kognitif dan Psikomotor pada Materi Membaca Pemahaman dengan Fokus Berpikir Evaluative di Sekolah Dasar - Nur Aini Asliatul Aziz; Chandra Chandra; Salmaini Safitri Syam (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Assessment is an integral part of the learning process that functions to determine the extent to which learning objectives have been achieved. This article discusses the assessment of cognitive and psychomotor domains in reading comprehension material with a focus on evaluative thinking. The main focus in evaluative reading is the ability of students to assess, criticize, and provide responses to information or texts read. Cognitive assessment is directed at measuring analytical, synthesis, and evaluation skills, while psychomotor assessment touches on aspects of real skills such as delivering oral responses or making written summaries. This study is expected to be a reference for educators in compiling holistic and balanced assessment instruments.